2012
DOI: 10.1016/j.cca.2012.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic calibrators for the analysis of total metanephrines in urine: Revisiting the conditions of hydrolysis

Abstract: Background: The quantification of total (free + sulfated) metanephrines in urine is recommended to diagnose pheochromocytoma. Urinary metanephrines include metanephrine itself, normetanephrine and methoxytyra-mine, mainly in the form of sulfate conjugates (60-80%). Their determination requires the hydrolysis of the sul-fate ester moiety to allow electrochemical oxidation of the phenolic group. Commercially available urine calibrators and controls contain essentially free, unhydrolysable metanephrines which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…The data for hydrolysis of NMN-S and MN-S were normally distributed accordingly to the Shapiro-Wilk test, whereas MT-S data were not normally distributed probably reflecting a higher variability for the deconjugation of this analyte. These results are in agreement with our previous work on urines [6], indicating that 30 min is ideal to hydrolyze sulfated metanephrines and that the nature of the matrix does not affect the hydrolysis rate as long as the pH is close to 1.0 (pH at 1.2 in our condition). However, our data are in total discrepancy with the work of Pagliary et al [7], who found a maximum concentration of the deconjugation of plasma S-NMN and S-MN submitted to acid hydrolysis after only 10 min and gradually lower concentrations of deconjugated metanephrines when incubation time was 20 and 30 min.…”
Section: Acid Hydrolysissupporting
confidence: 93%
See 2 more Smart Citations
“…The data for hydrolysis of NMN-S and MN-S were normally distributed accordingly to the Shapiro-Wilk test, whereas MT-S data were not normally distributed probably reflecting a higher variability for the deconjugation of this analyte. These results are in agreement with our previous work on urines [6], indicating that 30 min is ideal to hydrolyze sulfated metanephrines and that the nature of the matrix does not affect the hydrolysis rate as long as the pH is close to 1.0 (pH at 1.2 in our condition). However, our data are in total discrepancy with the work of Pagliary et al [7], who found a maximum concentration of the deconjugation of plasma S-NMN and S-MN submitted to acid hydrolysis after only 10 min and gradually lower concentrations of deconjugated metanephrines when incubation time was 20 and 30 min.…”
Section: Acid Hydrolysissupporting
confidence: 93%
“…The chemical protocols used for the synthesis of each sulfate metanephrines has been previously published [6]. All commercially available reagents and solvents (Fluka/Aldrich, Buchs, CH and Acros, Wohlen, CH) were used without further purification.…”
Section: Reagents Materials and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, efficiency of the acid hydrolysis conversion of sulfate conjugated to free metanephrines de-pends on pH, temperature, and time of incubation (21,22 ). This would not be a problem if calibrators and QC samples recapitulated the proportions of free and conjugated metabolites in patient samples.…”
Section: Free Vs Conjugated Metanephrinesmentioning
confidence: 99%
“…This would not be a problem if calibrators and QC samples recapitulated the proportions of free and conjugated metabolites in patient samples. However, commercially available calibrators and control samples used in assays of urine fractionated metanephrines are provided predominantly or entirely in the free form (18,21 ). Thus, unless deconjugation conditions are adequately controlled, concentrations of urine metanephrines in patient samples can suffer underestimation without parallel underestimation of controls (Fig.…”
Section: Free Vs Conjugated Metanephrinesmentioning
confidence: 99%